Subunit dynamics in Escherichia coli preprotein translocase. - Joly, J C (1994)
SecY, SecE, and band 1 copurify as the SecY/E integral membrane domain of Escherichia coli preprotein translocase. To measure the in vivo association of these polypeptides and assay possible exchange, plasmid-borne secY and secE genes were placed under control of the ara regulon and fused to DNA encoding the influenza hemagglutinin epitope. Cells were incubated with [35S]methionine, grown for a "chase" period, and then induced with arabinose to express epitope-tagged, nonradioactive SecY and SecE. Both the wild-type and epitope-tagged polypeptides assembled into functional, heterotrimeric SecY/E complex. However, immunoprecipitation with antibody to the epitope tag did not cross-precipitate radiolabeled SecY or SecE. Thus, these subunits normally associate stably in vivo.